Two-level five-phase voltage source inverter using medium and large vector switching technique with DSP implementation: article - Abd Ghani, Mohd Fais (2014)
Multiphase drives produce unwanted harmonic content that lead to distorted sinusoidal waveform which can be eliminate by switching technique. This research paper propose the design and analysis of experimental study on two-level five-phase voltage source inverter using space vector modulation technique perform by Digital Signal Processor (DSP) as switching control. The simulation and hardware design was carried out to identify the capability of medium and large vector combination technique in reducing low order harmonic which is high in large vector only technique and produce output voltage waveform close to sinusoidal. By using large and medium vector, low order harmonic especially 3rd and 7th order was reduce rapidly and produce less distortion output voltage.